(untitled) (Research, Society and Development, 2020)
In the current scenario of the 21st century, humanity faces a new threat. a virus titrated by Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), etiological agent of COVID-19. In times of pandemic, the use of websurveys is a great strategy for the collection of primary data. This study aimed to analyze the perception of academics about the pandemic of COVID-19. This study was developed in the municipality of Arapiraca and targeted undergraduate students from Campus I, state university of Alagoas. The research was developed in 3 stages, the first was the construction of a form using the Google Docs Forms platform, the second consisted of the distribution of the questionnaire through social networking applications (WhatsApp, Instagram) and was available to be answered for fifty-three days. In step three, the data was organized into Microsoft Excel spreadsheets. The survey had a total of sixty-two people who answered the questionnaire. The public reached by the survey was represented by citizens of the rural zone, with a percentage of 28.6%, and urban, with 71.4%, all of them Alagoanos. The majority (90.3%) believed that social isolation is an effective preventive measure in the absence of the vaccine. This cross-sectional research sought to investigate important information that could help researchers and health professionals develop awareness measures based on the target audience. Studies like this, using an alternative data collection methodology, are important to show that even in social distancing it is possible to do science.